2021
DOI: 10.1177/0022034520979639
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mandibular Canal Branches Related to Nociceptive Marker

Abstract: It is difficult to correlate the direction of mandibular canal branches (MCBs) with altered sensation in dental treatments. In contrast, calcitonin gene–related peptide (CGRP) is related to vasodilation, bone formation, and the interaction with the peripheral nervous system. Therefore, we investigated the detailed morphological characteristics of MCBs using cone-beam computed tomography (CBCT) and observation of the CGRP distribution around the MCB. The MCB measurements were evaluated using principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, importantly, this risk is higher in dentulous subjects. Previous reports suggested the presence of many lateral branches in the molars of the mandible [11], and high vascular density is noted from the third to rst molar of the mandible. These results suggest the risk of clinical complications at these molars.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, importantly, this risk is higher in dentulous subjects. Previous reports suggested the presence of many lateral branches in the molars of the mandible [11], and high vascular density is noted from the third to rst molar of the mandible. These results suggest the risk of clinical complications at these molars.…”
Section: Discussionmentioning
confidence: 83%
“…However, these previous ndings about the inferior alveolar nerve, artery and vein were mainly obtained through intramandibular measurements. Recently, we clari ed the existence of a lateral branch of the inferior alveolar nerve, artery and vein that emerges from this MC and reported that it exhibits speci c directionality [11].…”
Section: Introductionmentioning
confidence: 94%
“…The number of these mandibular canal branches is largely determined by the number of teeth and occlusion elements in the human mandible. 106 Since the presence of teeth helps to maintain the alveolar bone matrix, 107 when teeth are lost, nerve branches may disappear due to the absorption of alveolar bone. 106 , 108 …”
Section: Homestasis and Regulation Between The Nervous System And Jaw...mentioning
confidence: 99%
“… 106 Since the presence of teeth helps to maintain the alveolar bone matrix, 107 when teeth are lost, nerve branches may disappear due to the absorption of alveolar bone. 106 , 108 …”
Section: Homestasis and Regulation Between The Nervous System And Jaw...mentioning
confidence: 99%